Volume 3: 19th International Conference on Advanced Vehicle Technologies; 14th International Conference on Design Education; 10 2017
DOI: 10.1115/detc2017-68237
|View full text |Cite
|
Sign up to set email alerts
|

Do Technological Advancements Lead to Learning Enhancements?: An Exploration in Virtual Product Dissection

Abstract: Recent shifts into larger class sizes and online learning have caused engineering educators to rethink the way they integrate inductive, or active learning activities into their courses. One way engineering educators have done this is through the integration of new technological environments. However, little is known about how the type of technological environment utilized in active learning exercises impacts student learning and satisfaction. Thus, as a first step to understanding the impact of technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Product teardowns have been previously demonstrated to be very effective when performed in class by the students themselves [15], [17]- [21], but this mechanism for learning is often not conducted as it can be both time consuming and costly. For a large class, it can be difficult to monitor each student group to ensure everyone's participation and that the teardown is being performed correctly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Product teardowns have been previously demonstrated to be very effective when performed in class by the students themselves [15], [17]- [21], but this mechanism for learning is often not conducted as it can be both time consuming and costly. For a large class, it can be difficult to monitor each student group to ensure everyone's participation and that the teardown is being performed correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Welsh et al (2021) determined that students responded well to an augmented reality (AR) disassembly and inspection application and found that learning may be improved by enriched visualization, directed disassembly, and embedded hints [19]. In a separate study by Starkey et al (2017), the authors noted what while assessment results were not significantly different for different modes of virtual dissection (computer, iPad, and virtual reality), students' perceived learning and satisfaction was greatest with the virtual reality application [17]. While augmented and virtual-reality solutions are a promising method, the research discussed here required desktop and mobile-friendly technologies to be accessible for all students and thus relied heavily on video and interactive computer platforms.…”
Section: Introductionmentioning
confidence: 99%